The ACTH test in the diagnosis of hirsutism - Lima, Marco Fábio Prata; Nunes, Márcia Gaspar; Bonduki, Cláudio Emilio; Haidar, Mauro Abi; Lima, Geraldo Rodrigues; Baracat, Edmund Chada (São Paulo Medical Journal, 1997)
The ACTH test has been used to confirm the diagnosis of adrenal insufficiency and the classic and the non-classic adrenal hyperplasia due to the 3-HSD, 21 OH e 110H deficiencies. This article reviews the historical aspects of the use of ACTH in the diagnosis of hirsutism and points out its mains indications. In spite of new biological molecular advances in the diagnosis of adrenal enzymatic deficiencies, the use of the ACTH test can help the physician to predict both genothipus and fenothipus in populations with hyperandrogenic manifestations due to non-classical or late-onset congenital adrenal hyperplasia.